RELEVANSI PENDIDIKAN ISLAM DALAM MEWUJUDKAN MASYARAKAT MADANI - Dwi Putri , Febresti; Rahmadhani, Tiara; Kartika, Wahyuni; Gusmaneli, Gusmaneli (CV. ADIBA AISHA AMIRA, 2024)
In this article, some important points are discussed. First, the article highlights the development of academic potential through Islamic education. Complex and structured learning integrates general knowledge with Islamic religious values. This helps individuals to gain practical knowledge while engaging in Islamic religious practices. Second, the article explains the importance of developing social potential through Islamic education. Inclusive and supportive social learning helps individuals acquire communication, cooperation and harmonious interaction skills. In this way, a civil society based on Islamic values can be well formed. Third, the article discusses the development of moral and ethical potential through Islamic education. Individuals are taught Islamic religious values such as honesty, justice, and compassion. This helps form strong character and act responsibly in relationships with fellow humans.Finally, the article highlights the development of spiritual potential through Islamic education. Through worship and dhikr, individuals are given the opportunity to increase their awareness and relationship with Allah SWT. This spiritual dimension helps individuals seek peace and guidance in everyday life. Overall, this article concludes that Islamic education has great relevance in building civil society. In an era of rapid social change, Islamic education can be a foundation for improving morality, improving the quality of life, and maintaining a balance between material and spiritual progress. Therefore, Islamic education needs to receive serious attention from all parties, so that a civil society that is just, harmonious and has a religious perspective can be realized.